Effects of tetrodotoxin, Ca2+ absence, d-tubocurarine and vesamicol on spontaneous acetylcholine release from rat muscle - Dolezal, V; Tucek, S (The Journal of physiology, 1992)
1. Rat hemidiaphragms were incubated in a physiological low-K+ medium without stimulation and the amount of acetylcholine (ACh) released was measured radioenzymatically. Cholinesterases were inhibited by paraoxon. 2. In the presence of 1 microM tetrodotoxin (TTX), the amount of ACh released during a 2 h incubation was lowered by 40%. A similar decrease was observed in the absence of Ca2+ and in the presence of 10 microM-d-tubocurarine (dTC). The effects of TTX combined with Ca2+ removal, and of TTX combined with dTC were no greater than those of TTX, dTC or Ca2+ removal alone. TTX and dTC had no effect on the release of ACh from diaphragms 4 days after denervation. 3. The reduction of spontaneous ACh release observed in the presence of TTX or dTC or in the absence of Ca2+ is best interpreted on the assumption that about 40% of the ACh release was due to the impulse activity known to be generated in intramuscular motor nerve branches by the ACh which accumulates after the inhibition of cholinesterases. 4. In the presence of 1 and 10 microM vesamicol (AH5183, 2-(4-phenylpiperidino)-cyclohexanol), the release of ACh was also diminished by approximately 40%. Vesamicol did not augment the inhibition of release produced by TTX or by the omission of Ca2+.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Neuromuscular Depolarizing Agents; Calcium; Muscles; Tetrodotoxin; techniky in vitro; tubokurarin; svaly; cholinesterasy; denervace; acetylcholin; vápník; krysa rodu Rattus; Depression, Chemical; zvířata; potkani Wistar; časové faktory; Piperidines; tetrodotoxin; Acetylcholine; Denervation; Rats, Wistar; Cholinesterases; Male; bránice; In Vitro Techniques; Rats; chemická deprese; piperidiny; Animals; Diaphragm; mužské pohlaví; Time Factors; depolarizující myorelaxancia; Tubocurarine